KELAYAKAN BUKU TEKS BAHASA INDONESIA KURIKULUM MERDEKA UNTUK SMP KELAS VIII TERBITAN KEMENDIKBUD TAHUN 2021 - Nadya Ika Agustina; Siti Rohana Hariana Intiana; I Nyoman Sudika (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The suitability of Indonesian language textbooks for the Merdeka curriculum for class VIII junior high schools published by the Ministry of Education and Culture in 2021 is an important process to ensure that the material used is in accordance with the educational principles proposed by the Merdeka curriculum. The approach to this research method is descriptive qualitative. This type of research is analysis (content analysis). This means that this research carried out an analysis of the content in the Indonesian language textbook for the Independent Curriculum for Middle School Class VIII published by the Ministry of Education and Culture in 2021. The data collection technique used was note-taking technique. The results of research on the feasibility of the Merdeka Curriculum Indonesian language textbook for class VIII junior high schools published by the Ministry of Education and Culture in 2021 can be concluded that the Merdeka Curriculum Indonesian language textbook for class VIII junior high schools published by the Ministry of Education and Culture in 2021 is a textbook that is suitable for use as teaching material in the learning process.